Effectiveness of pranayama for mental disorders: a systematic review and meta-analysis of randomized controlled trials - Mütze, Christian; Mitzinger, Dietmar; Haller, Heidemarie (Frontiers in Psychiatry, 2025)
IntroductionThis review systematically assessed the evidence on the effectiveness and safety of prāṇāyāma, traditional yogic breathing techniques, for patients diagnosed with mental disorders.MethodsWe searched PubMed, PsycINFO, and Central until April 2024. We calculated standardized mean differences (SMDs) with 95% confidence intervals (CIs) from both intention-to-treat (ITT) and per-protocol (PP) data for symptom severity (primary outcome) and health-related quality of life and depression (secondary outcomes) using Hedges’ correction for small samples. For risk of bias (RoB) assessment, we used the Cochrane RoB 2 tool.ResultsWe included seven publications on six randomized controlled trials that examined 517 patients with posttraumatic stress disorder (PTSD), depression, and mixed non-psychotic mental disorders and compared prāṇāyāma to passive controls (wait list and attention control) or standard care (psychotherapy, electroconvulsive therapy, and antidepressants). Overall RoB was assessed with some concerns in two studies and as high in four studies. The meta-analyses of the ITT samples (SMD = −0.27, 95% CI = [−0.52, −0.03], I2 = 10%) as well as the PP samples (SMD = −0.35, 95% CI = [−0.57, −0.12], I2 = 0%) showed that prāṇāyāma significantly reduced post-intervention symptom severity in comparison to passive controls. When compared to standard care, both ITT and PP meta-analyses showed comparable results in reducing symptom severity. For secondary outcomes, only PP analyses on quality of life showed significantly higher post-intervention effects for prāṇāyāma in comparison to passive controls (SMD = 0.59, 95% CI = [0.31, 0.87], I2 = 20). No significant effects were found for depression. Sensitivity analyses excluding all studies with a high risk of overall bias revealed significant effects of prāṇāyāma on symptom severity and quality of life, but only in PP samples and in comparison to passive controls. Adverse events were more frequently associated with fast than with slow breathing techniques.DiscussionThis meta-analysis suggests short-term effects of prāṇāyāma when integrated in outpatient and inpatient care of mental disorders. In consideration of the overall high risk of bias and low number of analyzed patients, prāṇāyāma should not be used instead of standard therapies. Further research is needed to explore long-term effects and adequately assess adverse events.Protocol registration at ProsperoCRD42024550239